Understanding Entrepreneurial Aspirations Among Female Undergraduates in Bangladesh - Sikder Md. Fazlul Karim; K. M. Zahidul Islam (Asian Journal of Business and Accounting, 2026)
Manuscript type: Research paper Research aims: The study explores the factors impacting Bangladeshi female undergraduate students’ interest in entrepreneurship as a career path. The study examines the relationship between self-efficacy, risktaking, subjective norms, attitude, and perceived behavioural control and female students’ interest in entrepreneurship. Design/Methodology/Approach: The research employs a quantitative research design and relies on data collected using a Likert Five-point scale through a structured questionnaire. Survey data have been collected from 204 students enrolled in non-business courses in different universities of Bangladesh. Data were analysed using SPSS and Structural Equation Modeling (PLS-SEM) with Smart-PLS software version 4.0 to examine the effects of five dimensions of affiliation motivation on entrepreneurial aspirations. Research findings: The findings indicated a strong relationship between attitude, perceived behavioural control, and entrepreneurial intention. On the other hand, risk-taking, self-efficacy, and subjective norms are not strongly related to entrepreneurial intention. Implications: In addition to helping female undergraduate students better grasp the entrepreneurial decision-making process, the study’s findings may also aid entrepreneurs, academics, policymakers, and practitioners create an entrepreneurial ecosystem